LIGHT AND TEMPERATURE EFFECTS ON Sr/Ca AND Mg/Ca RATIOS IN THE SCLERACTINIAN CORAL ACROPORA SP - Reynaud S.; Ferrier-Pagès C.; Allemand D.; Meibom A.; Mostefaoui S.; Mortlock R.; Fairbanks R. (My University, 2007)
This study was designed to investigate the effect of light and temperature on Sr/Ca and Mg/Ca ratios in the skeleton of the coral Acropora sp. for the purpose of evaluating temperature proxies for paleoceanographic applications. In the first experiment, corals were cultivated under three light levels (100, 200, 400 μmol photons m-2 s-1) and constant temperature (27 °C). In the second experiment, corals were cultivated at five temperatures (21, 23, 25, 27, 29 °C) and constant light (400 μmol photons m-2 s-1). Increasing the water temperature from 21 to 29 °C, induced a 5.7-fold increase in the rate of calcification, which induced a 30% increase in the Mg/Ca ratio. In contrast, by increasing the light level by a factor of 4, the rate of calcification was increased only by a factor of 1.7, with a corresponding 9% increase in the Mg/Ca ratio. Thus, the relative change in the calcification rate in the two experiments (5.7 vs. 1.7) scales with the corresponding relative change in Mg/Ca ratio (30% vs. 9%). We conclude that there is a strong biological control on the incorporation of Mg. For Sr/Ca, good correlations were also observed with water temperature and the calcification rate induced by temperature changes. However, in sharp contrast with the Mg/Ca ratio, a temperature-induced 5.7-fold increase in the calcification rate only induced a 4.5% change (decrease) in the Sr/Ca ratio. An important finding for paleoceanographic applications is that the Sr/Ca ratio did not appear to be sensitive to changes in the light level, or to changes in calcification rate induced by changes in the light level. Thus, in this study, water temperature was found to be the dominant parameter controlling the skeletal Sr/Ca ratio. © 2006 Elsevier Inc. All rights reserved.